1996
DOI: 10.1136/emj.13.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital transfer of the critically ill trauma patient: the potential role of a specialist transport team in a trauma system.

Abstract: (JAccid Emerg Med 1996;13:90-92)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…33 McGinn and associates retrospectively examined the transport of 192 multiple trauma and isolated head injury patients by a specialized transport team, as described above. 39 All but 4 were ground transports, with the longest transport being 120 miles. Eighty-three of the multiple trauma patients required mechanical ventilation.…”
Section: The Transport Teammentioning
confidence: 99%
“…33 McGinn and associates retrospectively examined the transport of 192 multiple trauma and isolated head injury patients by a specialized transport team, as described above. 39 All but 4 were ground transports, with the longest transport being 120 miles. Eighty-three of the multiple trauma patients required mechanical ventilation.…”
Section: The Transport Teammentioning
confidence: 99%
“…Configurations can be nurse-paramedic or physician-nurse combination (Oakley, 1999;Blackwell, 2002;Barbara, 2003). Alternative personnel or specialized transport teams may be necessary depending on specific patient conditions (McGinn et al, 1996;Vos et al, 2004). There is still no worldwide accepted standard for assigning accompanying personnel for IFT (Markakis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…31 Mortality, where reported, reached always low rates. McGinn et al found 24 Descriptive, perspective 2 years 39 Ground; MICU 2 major complications (5%), among which one death, and 2 deaths within 6 hours from the arrival time (leukemia/sepsis) Uusaro et al 25 Cohort one lonely death in a series of 1305 transported patients 23 and two patients (among 39 critically ill transportations) died within 6 h from the arrival to the referral hospital reported by Gebremichael et al 24 Basically, major complications occurring during inter-hospital transports, especially those related to clinical condition, 28 are nearly superposed to the events reported in papers about intra-hospital transfers (Table 2). Conversely, technical incidents represent a typical feature of inter-hospital transport.…”
Section: Inter-hospital Transport Complicationsmentioning
confidence: 99%